Applying fulvic acid for sediment metals remediation: Mechanism, factors, and prospect - Song, Chuxuan; Sun, Shiquan; Wang, Jinting; Gao, Yang; Yu, Guanlong; Li, Yifu; Liu, Zhengqian; Zhang, Wei; Zhou, Lean (Frontiers in Microbiology, 2023)
Fulvic acid (FA) has been shown to play a decisive role in controlling the environmental geochemical behavior of metals. As a green and natural microbial metabolite, FA is widely used in environmental remediation because of its good adsorption complexation and redox ability. This paper introduces the reaction mechanism and properties of FA with metals, and reviews the progress of research on the remediation of metal pollutant by FA through physicochemical remediation and bioremediation. FA can control the biotoxicity and migration ability of some metals, such as Pb, Cr, Hg, Cd, and As, through adsorption complexation and redox reactions. The concentration, molecular weight, and source are the main factors that determine the remediation ability of FA. In addition, the ambient pH, temperature, metal ion concentrations, and competing components in sediment environments have significant effects on the extent and rate of a reaction between metals and FA during the remediation process. Finally, we summarize the challenges that this promising environmental remediation tool may face. The research directions of FA in the field of metals ecological remediation are also prospected. This review can provide new ideas and directions for the research of remediation of metals contaminants in sediments.